Assessment of existing structures under climate change - Johan V. Retief (Acta Polytechnica CTU Proceedings)
Assessment of the influence of human activities on recent, current, and future global and regional climate conditions and extremes has advanced sufficiently to provide a reasonable measure of its impact across the globe. The lack of concurrent adaptation of the design base for load bearing structures results mainly from the absence of a clear signal that climate change will have a significant effect on the climate actions that are accounted for in the structural design basis. The recent IPCC assessment of the physical science basis of climate change reports significant advances in observing and projecting changes in weather and climate extremes due to human influences. This provides an opportunity to reassess projections of future climate action conditions. Whilst the IPCC assessment confirms previous indications that, for example extreme wind will respond moderately globally, improvements in understanding and projecting changes show that trends will be overshadowed by uncertainties. The implication is that the design base will need to account for increasing uncertainties as climate actions are projected into the future, over the service life of existing structures, as well as those designed to current standards. The design base consequently in advance need to reflect continuous changes of existing structures.